Pentingnya Metodologi Penelitian Dalam Pendidikan Islam - Efendi, Indra; Sesmiarni, Zulfani (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2022)
The writing of this research was conducted to provide an overview of the importance of research methodology in Islamic Education in order to develop Islamic Education methods in today's modern era. Research methodology as a science for studying research should be understandable to Muslim scientists. all aimed at increasing knowledge in Islamic thought. This study uses a library research method of literature review which is descriptive-analytic in nature. So it can be concluded that the research method The research method is a scientific way to obtain data or information from the Koran, al-Hadith and the opinions of Islamic education scholars and experts as they are and not as they should be with specific purposes and uses. In general, the criteria for good Islamic education research are basically the same as other educational research. However, good research will have good value if the criteria are carried out according to the procedure. Results that are lacking in one or more of the criterion factors will invalidate the research